Gaby Amarantos, vestida para causar: interfaces entre moda e comunicação - VASCONCELOS NETO, Dilermando Gadelha de (Associação Nacional dos Programas de Pós-Graduação em Comunicação, 2022)
After the perception of a constant use of a communicational dimension of fashion in the researches that composes the fashion studies, mainly in the US and Europe, we propose to reflect on how some contemporary developments in the communication field contributes to stress some processes on the fashion studies. Especially because of a common preoccupation with the interactional/relational dimension on the two fields. Along with the presentation of our propose of interface, we dedicate to the analysis of the costumes used by the Pará’s singer Gaby Amarantos, due to point how this interface perspective applies to the study of empirical cases.